A STUDY OF GAMIFICATION CONCEPT OF INNOVATIVE LEARNING - Poondej, Chanut; Lerdpornkulrat, Thanita (Journal of Education and Innovation, 2020)
The aim of this study was to examine the results of applying gamification concept to the classroom. We measured teacher and student’s satisfaction, students’ liking to the subject, student motivation, and engagement in learning. The quasi-experimental nonequivalent-control group design was used with 78 students in the treatment groups and 112 students in the control groups. The results showed that 1) in the treatment groups, student’s liking for the subject and engagement in learning were higher than the control group with statistical significance of .01, 2) students’ behaviors in the treatment group reported listening to lecture, focusing on the learning, engaged interaction with instructor, fun and excitement, which were higher than students in the control group with statistical significance of .01, and 3) teachers were satisfied with applying gamification concept to the classroom.